Tumor-targeted/reduction-triggered composite multifunctional nanoparticles for breast cancer chemo-photothermal combinational therapy - Yun Yang; Danrong Hu; Yi Lu; Bingyang Chu; Xinlong He; Yu Chen; Yao Xiao; Chengli Yang; Kai Zhou; Liping Yuan; Zhiyong Qian (Elsevier, 2022)
Breast cancer has become the most commonly diagnosed cancer type in the world. A combination of chemotherapy and photothermal therapy (PTT) has emerged as a promising strategy for breast cancer therapy. However, the intricacy of precise delivery and the ability to initiate drug release in specific tumor sites remains a challenging puzzle. Therefore, to ensure that the therapeutic agents are synchronously delivered to the tumor site for their synergistic effect, a multifunctional nanoparticle system (PCRHNs) is developed, which is grafted onto the prussian blue nanoparticles (PB NPs) by reduction-responsive camptothecin (CPT) prodrug copolymer, and then modified with tumor-targeting peptide cyclo(Asp-d-Phe-Lys-Arg-Gly) (cRGD) and hyaluronic acid (HA). PCRHNs exhibited nano-sized structure with good monodispersity, high load efficiency of CPT, triggered CPT release in response to reduction environment, and excellent photothermal conversion under laser irradiation. Furthermore, PCRHNs can act as a photoacoustic imaging contrast agent-guided PTT. In vivo studies indicate that PCRHNs exhibited excellent biocompatibility, prolonged blood circulation, enhanced tumor accumulation, allow tumor-specific chemo-photothermal therapy to achieve synergistic antitumor effects with reduced systemic toxicity. Moreover, hyperthermia-induced upregulation of heat shock protein 70 in the tumor cells could be inhibited by CPT. Collectively, PCRHNs may be a promising therapeutic way for breast cancer therapy.